Digestibility of Dry Matter is Better and Manure Output is Lower in Growing Cattle Limit-Fed a High-Energy Diet During the Growing Phase Compared to a Traditional Roughage-Based Diet Fed for Ad Libitum Intake - M. A. Scilacci; E. Titgemeyer; S. P. Montgomery; T. J. Spore; A. J. Tarpoff; T. G. O'Quinn; W. R. Hollenbeck; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:Evaluate the impact on intake and digestion of a high-energy diet limit-fed at 85% of thead libitumdaily consumption of a roughage-based diet on a dry matter (DM) basis compared to a traditional roughage-based growing diet in growing cattle. Study Description:Eight ruminally cannulated crossbred Angus heifers (body weight = 450 ± 24 lb) were used in a cross-over design with two consecutive 15-day periods at the Kansas State University Beef Stocker Unit. Two dietary treatments were fed: (1) 45 Mcal of net energy for gain (NEg) per 100 lb of DM fed forad libitumDM intake (45AL), or (2) 60 Mcal NEgper 100 lb of DM limit-fed at 85% of 45AL diet intake on a DM basis (60LF85%). Both diets contained 40% of DM as Sweet Bran (Cargill Animal Nutrition, Blair, NE). Heifers were fed once daily at 10:00 a.m. Each 15-day period included 10 days for diet adaption, 4 days for fecal sampling, and 1 day for ruminal sampling. Daily nutrient intake was measured and apparent total-tract diet digestibility using chromic oxide (Cr2O3) marker was determined. Results:Ruminal pH was greater (P<0.01) from 10:00 p.m. to 10:00 a.m. just before feeding for heifers fed 60LF85% than 45AL heifers. Diet digestibility was improved by 5.2% (P<0.01) and fecal DM output 35% lower (P<0.01) in heifers fed 60LF85% than heifers fed 45AL. The Bottom Line:Heifers limit-fed a high-energy diet based on corn and Sweet Bran had greater ruminal pH during the overnight hours, better diet digestibility, and reduced output of manure than heifers full-fed a traditional roughage-based diet.
Keywords: Limit feeding; growing cattle; diet digestibility